2016
DOI: 10.1016/j.drudis.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

In vitro models for assessing therapeutic angiogenesis

Abstract: Arterial obstruction leading to ischemia causes a reduction of oxygen and nutrient supply to distal tissues. The physiological response to tissue ischemia triggers a cascade of events that results in the development of accessory vasculature to increase local tissue perfusion and to salvage tissue. However, this adaptive mechanism of repair is suboptimal in some patients. Therapeutic angiogenesis aims to stimulate new blood vessel formation via the local administration of proangiogenic agents or cell therapy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…As depicted from Figure 5, 5% and 10% FBS supported healthy micro-tissue formation with high ratio of live cells. These results were in agreement with Sanz-Nogués and O'Brien [18] where they indicated the requirement of using low FBS concentrations to understand the vascularization of endothelial cells even in 2D culture. Furthermore, Rouwkema and Khademhosseini [14] also suggested that biological cues that guides the vascularization process in tissue engineered scaffolds needs to clearly identified to understand major factors in vascularization.…”
Section: Discussionsupporting
confidence: 90%
“…As depicted from Figure 5, 5% and 10% FBS supported healthy micro-tissue formation with high ratio of live cells. These results were in agreement with Sanz-Nogués and O'Brien [18] where they indicated the requirement of using low FBS concentrations to understand the vascularization of endothelial cells even in 2D culture. Furthermore, Rouwkema and Khademhosseini [14] also suggested that biological cues that guides the vascularization process in tissue engineered scaffolds needs to clearly identified to understand major factors in vascularization.…”
Section: Discussionsupporting
confidence: 90%
“…The scratch assay employed in this study mimics the endothelial cell migration during wound healing in vivo [27,28]. Here, a scratch assay was used to assess the capacity of MSC-secreted factors present in MSC-conditioned medium to stimulate endothelial cell (HUVEC) migration subsequent to creating a scratch through the HUVEC monolayer.…”
Section: Angiogenic Capacity Comparable In Mscs Isolated From Donors mentioning
confidence: 99%
“…The tubule assay employed in this study mimics the endothelial cell differentiation during wound healing in vivo [28] by assessing the capacity of MSC-secreted factors to stimulate endothelial cell tubule formation over 18 h on a Matrigel substrate. Here, HUVEC cells were combined with either αMEM (negative control), EGM (positive control), or conditioned medium from either donor cohort before being plated on Matrigel.…”
Section: Angiogenic Capacity Comparable In Mscs Isolated From Donors mentioning
confidence: 99%
“…Angiogenesis is a complex process that is involved in disease progression and tissue repair. The multifaceted, spatiotemporal mechanisms of angiogenesis along with the relatively high cost and technical skill level associated with in vivo studies make it difficult to rapidly and efficiently evaluate the efficacy of both biomaterials and molecular therapies targeting vascular network formation [1][2][3][4][5][6][7][8][9][10][11]. In vitro models provide a less expensive, more controlled, and reproducible platform for better quantification of isolated angiogenic processes in response to biomaterial, biochemical, or biophysical stimuli [3,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%